Research trends and hotspots in the tumor microenvironment of ovarian cancer: a bibliometrics and visualization study from 2005 to 2024 - Wang, Jingwen; Yin, Guohao; Hou, Fangyu; Yin, Xiangyu; Liu, Tao (Frontiers in Immunology, 2025)
BackgroundThe tumor microenvironment (TME) is crucial in influencing the progression and therapeutic response of ovarian cancer.MethodThis study conducted a comprehensive bibliometric and visualization analysis of research trends and focal areas concerning the ovarian cancer microenvironment from 2005 to 2024. A total of 1,720 pertinent articles were identified from the Web of Science Core Collection (WoSCC) database.ResultsThe analysis revealed a notable increase in research activity on the TME of ovarian cancer, particularly during the period from 2019 to 2022. The United States and China were the most active countries in this field, and the University of Texas System was the scientific research institution with the largest number of articles. Cancer Research and Clinical Cancer Research were the most cited journals. Weiping Zou and Anil K Sood were recognized as the most cited researchers. The study systematically identified key research hotspots within this field, encompassing immune checkpoint inhibitors, single-cell RNA sequencing technology, the TME heterogeneity, the TGFβ signaling pathway, and the impact of PARP inhibitors on the tumor immune microenvironment (TIME).ConclusionThis study provides a valuable reference for the evolution and prospective directions of TME research in ovarian cancer, underscoring the critical importance of a comprehensive understanding of the TME to enhance treatment strategies for ovarian cancer.